The effects of β-lactam antibiotics and hygromycin B on de novo shoot organogenesis in apple cv. Golden Delicious - Stanišić Mariana; Ninković Slavica; Savić Jelena; Ćosić Tatjana; Mitić Nevena (Archives of Biological Sciences, 2018)
Since the genetic transformation of the apple is strongly genotype-dependent and generally inefficient, the evaluation of factors affecting shoot regeneration are crucial for the establishment of a successful transformation process. In this report, we evaluated the effects of the β-lactam antibiotics meropenem and timentin on in vitro regeneration via de novo shoot organogenesis from leaf explants of apple cv. Golden Delicious, as well as on the growth of the Agrobacterium tumefaciens strain EHA 105, and compared them with the commonly used β-lactam cefotaxime. Also, we report for the first time the effect of hygromycin B as a selective agent in the domesticated apple, as regards shoot regeneration and shoot multiplication efficiency. We observed that cefotaxime and timentin at concentrations higher than 100 mg L-1 were sufficient to prevent Agrobacterium growth during a two-week period, while meropenem exhibited an inhibitory effect on bacterial growth at all tested concentrations (25-150 mg L-1). Cefotaxime at a concentration of 300 mg L-1 increased the number of regenerated shoots per explant (9.39) in comparison with the control (7.67). In contrast to cefotaxime, meropenem and timentin caused a decrease in shoot regeneration efficiency, but larger and more developed shoots were obtained on meropenem (25-125 mg L-1) after the same period of cultivation. Hygromycin B at a concentration of 5 mg L-1 or higher completely inhibited shoot regeneration and induced explant tissue necrosis. Therefore, the selection procedure with a final concentration of 4 mg L-1 throughout organogenesis and 10 mg L-1 for further shoot growth and multiplication is recommended for an efficient transformation process in apple cv. Golden Delicious. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. ON173015]